Personalized Screening Protocols for Gestational Diabetes Mellitus: Enhancing Early Detection and Management for Improved Maternal and Neonatal Outcomes - Madugalle, Madugalle Edirisinghe Mudiyanselage Yasassri Devinda Bandara; Rathnayake, Rathnayake Mudiyanselage Chathura; Rajayohan, Tharunya; Kotigala, Dhanushka Srikantha; Ruwanpathirana, Susil Anura (Medical Science: Trends and Innovations Vol. 9, 2025)
Background: Gestational Diabetes Mellitus (GDM) poses significant risks to both mothers and fetuses, with an escalating global prevalence. GDM is becoming more prevalent in recent years. Women who are usually diagnosed with GDM have normal glucose tolerance following delivery. But during the next 20 years of life, the majority of them may suffer from chronic diabetes, making GDM one of the most predictive factors for the development of chronic diabetes later in life. Aim: This study addresses the critical need for timely GDM detection in high-risk pregnancies. By comparing the efficacy of the standard 28-week oral glucose tolerance test with an early 20-week screening, the research aims to enhance preventive interventions and minimise complications, contributing valuable insights for optimal GDM management in high-risk populations. Methodology: Conducted at Teaching Hospital Peradeniya, Sri Lanka, this prospective cohort study investigated early GDM diagnosis using a 20-week OGTT in high-risk pregnancies with negative booking screens. The research involved 385 singleton pregnancies, assessing risk factors such as GDM history, family history of diabetes, macrosomia, BMI > 30 kg/m2, polycystic ovary syndrome, and advanced maternal age. The study included evaluating GDM incidence at 20 and 28 weeks, analysing risk factor associations, and determining the efficacy of early OGTT compared to routine testing. The data analysis aimed to establish the significance of a 20-week OGTT, identify the main contributory risk factors, and propose an optimal timing for GDM screening in high-risk pregnancies. The data analysis for this study employed the Statistical Package for the Social Sciences (SPSS) software. Descriptive statistics were used to outline the incidence of GDM at 20 weeks, 28 weeks, and the absence of GDM within the study cohort. Results: In the study involving 385 high-risk pregnant women, the incidence of gestational diabetes mellitus (GDM) was 7.27% at 20 weeks, 10.91% at 28 weeks, and 81.82% without GDM. Significant associations were found between GDM at 20 weeks, a history of GDM (78.57%), and a family history of diabetes (28.57%) (p = 0.011, 0.010, respectively). Polycystic ovarian syndrome and advanced maternal age were significantly associated with GDM at 28 weeks (p = 0.016, 0.008, respectively). Previous macrosomia or body mass index was not associated with GDM at 20 or 28 weeks. Notably, the McNemar test revealed no significant association between GDM cases at 20 and 28 weeks. Discussion and Conclusion: This study emphasizes the need for early diagnosis of GDM at 20 weeks in high-risk pregnancies. Effective GDM management mitigates short-term complications but raises concern about long-term impacts on offspring. Risk factors for early GDM include family history and prior GDM. The study’s strengths lie in its comprehensive analysis. However, the single-cohort nature and lack of data on maternal and fetal outcomes following early vs. standard diagnosis of GDM limits the generalizability of study findings. Limited evidence prompts a call for further well-designed research to determine the optimal intervention window focusing on personalised screening approaches and improving gestational age assessments. Overall, this study contributes to the ongoing discourse on early GDM management, highlighting the need for tailored prenatal care.